CsRAB, a R2R3-MYB transcription factor from purple tea (Camellia sinensis), positively regulates anthocyanin biosynthesis - Wu, Hualing; Pan, Yayan; Ni, Erdong; Qin, Dandan; Fang, Kaixing; Wang, Qing; Yang, Chengwei; Luo, Ming; Liu, Jun (Frontiers in Plant Science, 2024)
In tea (Camellia sinensis), anthocyanins are important secondary metabolites that are linked to leaf color. Anthocyanin biosynthesis is a complex biological process, in which multiple genes including structural and regulatory genes are involved. Here, we describe the cloning and characterizing of a new R2R3-MYB transcription factor gene, CsRAB, isolated from purple tea variety 'Hongfei'. Consistent with its predicted role as a transcription factor, the CsRAB protein localized to nuclei when expressed in onion (Allium cepa) epidermal cell. A dual-luciferase reporter assay demonstrated that CsRAB acts as a transcriptional activator in vivo. CsRAB overexpression in Arabidopsis seedlings led to higher expression levels of anthocyanin biosynthesis-related genes, and consequently, purple stems and higher anthocyanin contents were exhibited in overexpressing lines compared to wild type. The results indicated that CsRAB plays critical roles in positively regulating anthocyanins biosynthesis in tea plants.